Whole brain radiotherapy with adjuvant or concomitant boost in brain metastasis: dosimetric comparison between helical and volumetric IMRT technique. Issue 1 (December 2016) - Borghetti, Paolo; Pedretti, Sara; Spiazzi, Luigi; Avitabile, Rossella; Urpis, Mauro; Foscarini, Federica; Tesini, Giulia; Trevisan, Francesca; Ghirardelli, Paolo; Pandini, Sara; Triggiani, Luca; Magrini, Stefano; et al.
Abstract Background To compare and evaluate the possible advantages related to the use of VMAT and helical IMRT and two different modalities of boost delivering, adjuvant stereotactic boost (SRS) or simultaneous integrated boost (SIB), in the treatment of brain metastasis (BM) in RPA classes I-II patients. Methods Ten patients were treated with helical IMRT, 5 of them with SRS after whole brain radiotherapy (WBRT) and 5 with SIB. MRI co-registration with planning CT was mandatory and prescribed doses were 30 Gy in 10 fractions (fr) for WBRT and 15Gy/1fr or 45Gy/10fr in SRS or SIB, respectively. For each patient, 4 "treatment plans" (VMAT SRS and SIB, helical IMRT SRS and SIB) were calculated and accepted if PTV boost was included in 95 % isodose and dose constraints of the main organs at risk were respected without major deviations. Homogeneity Index (HI), Conformal Index (CI) and Conformal Number (CN) were considered to compare the different plans. Moreover, time of treatment delivery was calculated and considered in the analysis. Results Volume of brain metastasis ranged between 1.43 and 51.01 cc (mean 12.89 ± 6.37 ml) and 3 patients had double lesions. V95% resulted over 95 % in the average for each kind of technique, but the "target coverage" was inadequate for VMAT planning with two sites. The HI resulted close to the ideal value of zero in all cases; VMAT-SIB, VMAT-SRS, Helical IMRT-SIB and Helical IMRT-SRS showed mean CI of 2.15, 2.10, 2.44 and 1.66, respectively (optimal range: 1.5–2.0). Helical IMRT-SRS was related to the best and reliable finding of CN (0.66). The mean of treatment time was 210 s, 467 s, 440 s, 1598 s, respectively, for VMAT-SIB, VMAT-SRS, Helical IMRT-SIB and Helical IMRT-SRS. Conclusions This dosimetric comparison show that helical IMRT obtain better target coverage and respect of CI and CN; VMAT could be acceptable in solitary metastasis. SIB modality can be considered as a good choice for clinical and logistic compliance; literature's preliminary data are confirming also a radiobiological benefit for SIB. Helical IMRT-SRS seems less effective for the long time of treatment compared to other techniques.